The outcome of postoperative paresthesia of inferior alveolar nerve after surgical removal of mandibular third molar using Orthopantomogram (OPG) versus Cone-beam CT - Sajid, Ali Hassan (Journal of Fatima Jinnah Medical University, 2021)
Background: Periapical and Orthopantomogram (OPG) are the most commonly used radiographs for assessment of the relationship of lower 3rd molar roots with the inferior alveolar canal. Panoramic radiographs provide inadequate information of the buccolingual relationship between the roots of the 3rd molar & mandibular canal being two-dimensional (2D) in nature. To verify the relationship in three (3D) dimensions and to make a predictable treatment plan, traditional investigations may be supplemented by using CBCT. Cone-beam computerized tomography (CBCT) is an office-based radiography technique used to assess the three-dimensional relationship of lower 3rd molar roots with inferior alveolar nerve. Patients and methods: This comparative-cross sectional study was conducted at the Department of Oral and Maxillofacial Surgery, Fatima Memorial Hospital (FMH), Lahore from 1st January 2019 till 30th June 2019. A total of 124 patients requiring removal of lower wisdom tooth were enrolled and then divided into two groups (62 in each) randomly. OPG was used for diagnosis of impacted lower 3rd molars in Group A patients while CBCT for diagnosis in Group B patients. A self-designed Performa was used to collect the data and final information was collected after 3 months of follow-up. Data analysis was performed using SPSS 20. A chi-square test was used to compare the postoperative paraesthesia between the OPG group and CBCT group patients. A p-value <0.05 was taken as significant. Results: The occurrence of postoperative paresthesia between the two groups is significantly different; being a low percentage in the CBCT group at 2nd, 7th day and after 3 months follow-up visits with a p-value of 0.019, 0.019, and 0.005 respectively. On 3 months follow up, the distribution of paraesthesia between the two groups is significantly different; 20 patients (32.25%) in OPG group A and those of 7 (11.29%) in CBCT group B experienced paresthesia with a p-value of 0.005. Conclusion: It is better to use CBCT to improve the postoperative paraesthesia for lower third molar surgical extraction.